EVALUATION OF SYNERGISTIC EFFECT OF THUJAORIENTALIS WITH CIPROFLOXACIN AGAINST ESCHERICHIA COLI - Mateen, Hajra; Faisal, Rizwan; Khizar, Syeda Huma; Habib, Syed Hamid (Pakistan Armed Forces Medical Journal, 2020)
Objectives: To determine the antimicrobial effect of Thujaorientalis (TO) and ciprofloxacin alone against Escherichia Coli (E.Coli). To compare the combined antimicrobial effect of TO and ciprofloxacin against E. Coli.Study Design: Laboratory experimental study. Place and Duration of Study: This in vitro study was performed at Khyber Girls Medical College, Peshawar, from Jan to Jul 2018.Methodology: Antibacterial activity of TO extracts alone and in combination with ciprofloxacin against E.Coli was evaluated by using disc-diffusion and minimum inhibitory concentration method. E. coli clinical strains were collected from Rehman Medical Institute and Northwest General Hospital Peshawar, and American Type Culture Collection [ATCC] strains (number 23922) of these bacteria were collected from Agriculture University Peshawar. The organisms were tested six times with crude extract and fractionation with different solvents such as n-hexane, chloroform, ethyl acetate and butanol at concentrations of 1, 4, 8, 12, 16, 20, 24, 30 and 36 mg/ml. The mean minimum inhibitory concentration and fractional inhibitory concentration index were obtained to report the synergism. The data was analysed using SPSS version 21.Results: Antibacterial activity of different fractions of plant was interpreted as synergy, indifference and antagonism against E.Coli. Fractional inhibitory concentration index for E.Coli ranged from 3 to 1.05, which showed antagonism and indifferent effect of combination of plant extract with ciprofloxacin.Conclusion: Synergism between TO and ciprofloxacin was shown against E.Coli by disc diffusion method while no synergistic effects were found through minimum inhibitory concentration.